150 Utilization of Fluorescent In Situ Hybridization (FISH) Probe Panels in Routine Clinical Hematopathology Practice: Part I. Lymphoid and Plasma Cell Disorders. (11th January 2018) - Harrison, Harold; Tutaeva, Victoria; Dorion, Patrick; Haynes, Amanda; Tsang, Patricia; Zhang, Kai; Zhang, Xiaohong; Kip, Nefize
Abstract: Objectives: The Geisinger Medical Laboratories' hematopathology service supports an integrated healthcare system in central Philadelphia of numerous physician sites, seven hospitals, and three cancer and eight regional multispecialty clinics, while serving a population of 3 million. Like others, we have incorporated hematologic fluorescence in situ hybridization (FISH) staining as a superior procedure to standard cytogenetics, especially in lymphoid and plasma cell disorders, because of its improved diagnostic/prognostic yield in interphase staining. However, as advanced technologies such as FISH come under scrutiny for expense and optimal utilization review, we sought to establish statistics of utilization and outcomes that verify attainment of appropriate results, with benchmarks of performance parameters and utilization in monoclonal gammopathy of undetermined significance (MGUS), multiple myeloma (MM), chronic lymphocytic leukemia (B-CLL) and high-grade B-cell lymphoma (HG-BCL). Methods: Data were reviewed retrospectively for 4, 191 HemeFISH panels performed from January 2013 to December 2016 on bone marrow, peripheral blood, and lymph nodes. Approximately one-third of cases (1, 525, 36.3%) were lymphoid/plasma cell; the remaining were myeloid. Samples were stained with diagnosis-specific panels of FISH probes at a reference laboratory (Neogenomics, Ft. Myers, FL) and interpreted by the pathologists at Geisinger Health System (GHS). Results: Excluding repeat and duplicate testing, there were 990 unique cases, with the distribution of FISH panel results in the table below: Conclusion: FISH abnormalities detected appear to be in line with published literature for the observed cytogenetic abnormalities and frequencies. FISH panels provide improved diagnostic/prognostic yield in B-CLL followed by HG-BCL, MM, and MGUS. This analysis yields baseline benchmarks for frequency and outcomes against which performance improvements can be made.